The Implementation Problem Solving Methods of Learning Arabic Lesson: Taṭbīq Asālīb Ĥalli al-Musykilāt fī Ta’allum al-Lugah al-‘Arabiyyah - Budiman, Agus; Aprilia, Ayu; Zain, Auriza Luthfiah (Study Program of Arabic Language Teaching, 2023)
This study examines the process problem-solving method of Arabic lessons at Gontor for the girl's first campus, which is suitable for his students to get good results and according to expectations.The Problem-Solving method provides understanding by stimulating students to pay attention, examine, and think about a problem to analyze the problem further to solve the problem. Analyzing is the concept of combining thoughts with motor activities to solve problems. Sources of data used in this study are primary and secondary data sources. This study uses data collection techniques with interview methods, observation methods, and documentation methods. The technique of guaranteeing the validity of the data in this study is the triangulation of sources and data collection techniques. Qualitative data analysis in this study is descriptive data consisting of three activities simultaneously. Namely data reduction, data presentation, and conclusion. Based on the results of research and analysis, it can be found that the use of problem-solving methods in Arabic lessons in one intensive 2021-2022 is in the problem-solving method, the teacher uses steps such as problem clarification, expression of opinion, evaluation, and implementation. Then, the supporting factors for learning Arabic using problem-solving methods are knowledge, understanding, and application, while the inhibiting factors for learning Arabic using problem-solving methods are time, learning difficulties, and use.